ENHANCE STUDENT'S GROWTH MINDSET: EXPLORING THE INTERVENTION ALL AROUND THE WORLD USING BIBLIOMETRIC ANALYSIS - Ma'rifatin Indah Kholili; Nandang Rusmana; Ahman Ahman; Nandang Budiman; M Sholehuddin; Arifah Wulandari (PEDAGOGIK : JURNAL PENDIDIKAN, 2026)
Growth mindset therapy research has grown considerably in the past decade. Intervention effectiveness is assessed, not global design, delivery, and implementation changes. This study used bibliometrics to map 2010–2025 growth mindset intervention structural change. From Publish or Perish, Google Scholar included 100 most-cited intervention studies. Topic trends, intervention typologies, and bibliometric mapping patterns emerged from VOSviewe co-occurrence and co-authorship studies. Quick, digital, scalable, and low-cost interventions replaced classroom ones. Growth mindset is now a cross-domain intervention to improve academic, mental, resilience, and career outcomes. Most influential research are from Western countries, mostly the US, indicating limited cross-cultural validation. Short and online interventions dominated the five intervention typologies because to their scalability and usefulness. This study provides a growth mindset intervention research approach and finds a significant scalability-impact trade-off. Systematic reviews, meta-analyses, and cross-cultural empirical investigations should examine intervention faithfulness, contextual variables, and cultural adaptability in addition to efficacy.